PHYSICAL AND CHEMICAL METHODS FOR FLAVONOIDS CONTENT DETERMINATION IN SOPHORA FLAVESCENS ROOTS - A. B. Samoryadova (Фармация и фармакология (Пятигорск), 2015)
The article presents a study on the identification methodology elaboration of flavonoids in Sophora flavescens roots using chemical reaction and TLC method. We have also developed methods of quantitative determination of flavonoids sum into raw materials by differential spectrophotometry method.